Two laser beams interaction in photonic crystal fibers infiltrated with highly nonlinear materials - Murek, Mateusz; Rutkowska, Katarzyna Agnieszka (Photonics Letters of Poland, 2014)
In this letter, the results of experimental tests on the discrete light propagation in photonic liquid crystal fibers (PLCFs) are presented. More precisely, this work is mainly inquiring into the matter how two laser beams simultaneously launched into PLCF can influence the optical properties of the fiber. For this purpose, a weak collinear probe beam at the different wavelength has been applied to monitor how the waveguide channel(s) is (are) decoupled from the rest of the matrix due to the influence of the pump laser beam. Firstly, low-power signal beam at the wavelength of 532nm has been co-launched axially with the pump beam (1064nm) to confirm a power-dependence of optical properties (induced by the pump) while observing the signal beam profile at the output facet of PLCF. Secondly, the beams from the same laser sources in the inverted configuration have been applied. Full Text: PDF References P.St.J. Russell, "Photonic Crystal Fibers", Science 299, 358 (2003). CrossRef E. Poli, A. Cucinotta, S. Selleri, Photonic Crystal Fibers. Properties and Applications (Springer, The Netherlands 2007). R.T. Bise, R.S. Windeler, K.S. Kranz, C. Kerbage, B.J. Eggleton, D.J. Trevor, Opt. Fiber Comm. Conf. Techn. Digest, 466 (2002). T.T. Larsen, A. Bjarklev, D.S. Hermann, J. Broeng, "Optical devices based on liquid crystal photonic bandgap fibres", Opt. Expr. 11, 2589 (2003). CrossRef I.L. Garanovich, S. Longhi, A.A. Sukhorukov, Y.S. Kivshar, "Light propagation and localization in modulated photonic lattices and waveguides", Phys. Rep. 518, 1 (2012). CrossRef F. Lederer, G.I. Stegeman, D.N. Christodoulides, G. Assanto, M. Segev, Y. Silberberg, "Discrete solitons in optics", Phys. Rep. 463, 1 (2008). CrossRef K.A. Brzdąkiewicz, U.A. Laudyn, M.A. Karpierz, T.R. Woliński, J. Wójcik, "Linear and nonlinear properties of photonic crystal fibers filled with nematic liquid crystals", Opto-Electron. Rev. 14, 287 (2006). CrossRef U.A. Laudyn, K.A. Rutkowska, R.T. Rutkowski, M.A. Karpierz, T.R. Woliński, J. Wójcik, "Nonlinear effects in photonic crystal fibers filled with nematic liquid crystals", Centr. Europ. J. Phys. 6(3), 612 (2008). CrossRef C.R. Rosberg, F.H. Bennet, D.N. Neshev, P.D. Ramussen, O. Bang, W. Krolikowski, A. Bjarklev, Y.S. Kivshar, "Tunable diffraction and self-defocusing in liquid-filled photonic crystal fibers", Opt. Expr. 15(19), 12145 (2007). CrossRef M. Vieweg, T. Gissibl, Y. Kartashov, L. Torner, H. Giessen, "Spatial solitons in optofluidic waveguide arrays with focusing ultrafast Kerr nonlinearity", Opt. Lett. 37, 2454 (2012). CrossRef K.A. Rutkowska, U.A. Laudyn, P.S. Jung, "Nonlinear discrete light propagation in photonic liquid crystal fibers", Phot. Lett. Poland 5(1), 17 (2013). CrossRef K.A. Rutkowska, U.A. Laudyn, P.S. Jung, "Discrete light propagation in photonic liquid crystal fibers", IEEE Xplore 2012, DOI: 10.1109/PGC.2012.6457983 CrossRef K.A. Rutkowska, U.A. Laudyn, P.S. Jung, "All-optical control of discrete light propagation in photonic liquid crystal fibers", IEEE Xplore 2013, CrossRef